Shear Strength of Directly and Indirectly Loaded Rectangular Self - Compacted Reinforced Concrete Deep Beams Containing Recycled Concrete as Coarse Aggregate - Alhussein, Thamer; Khudhair, Jamal (Anbar Journal of Engineering Sciences, 2020)
Deep beams with rectangular cross-sections are widely used in concrete structures. In the present study, reinforced concrete rectangular deep beams cast with self-compacted concrete (SCC) which contains recycled concrete as coarse aggregate (RCA) were tested under directly and indirectly loading conditions. In the experimental work, fifteen deep beams were investigated, the first parameter considered in this study was the shear span to effective depth (a/d) ratio. The other variable is the replacement ratio by which the normal coarse aggregate is replaced by RCA. The beams were cast without the use of shear reinforcement. During the tests, the response of the beams including the cracking load, the ultimate load, concrete strain, and mid-span deflection were recorded. Test results indicate that the presence of RCA caused a reduction in the values of cracking and ultimate loads. For instance, the cracking load was reduced by 9%, 23%, and 50% and the ultimate load was reduced by 2% , 23%, and 25% as RCA replacement increased by 25%, 50%, and 75% respectively for a/d ratio equals 1.0. Further, by increasing the a/d ratio, the ultimate load was decreased due to the lower contribution of arch action shear transfer in the beam with a higher (a/d) ratio.